Two rheologically different gastric mucus secretions with different putative functions - Taylor, Catherine; Allen, Adrian; Dettmar, Peter W.; Pearson, Jeffrey P. (Biochimica et biophysica acta, 2004)
Previous work has shown the presence of different mucin gene products and glycosylated species in gastric mucus secretions, however, the functional relevance of these differences is unclear. This study aimed to investigate rheologically, differences in the gel behaviour within gastric mucus samples using a pig model. Rheological measurements were made on a Bohlin CVO50 rheometer. Mucins were characterised by antigenicity, lectin reactivity and proteolytic fragmentation patterns. Two distinct mucus gel secretions, one compliant with and the other resistant to shear stress, were removed from the gastric mucosa. The two gels had different rheological behaviour profiles and exhibited structural differences in their constituent mucins. The shear-compliant mucus was located superficially to the adherent shear-resistant mucus layer and was shown not to be a proteolytic product of the latter. This study has demonstrated that there are two rheologically distinct mucus gel secretions with structural/compositional differences in the stomach. Rheological properties suggest that the adherent, shear-resistant gel could provide the mucus barrier in vivo while the shear-compliant gel could act primarily as a lubricant.